Nitrogen fertilizer application rate affects the dynamic metabolism of nitrogen and carbohydrates in kernels of waxy maize - Feng, Wanjun; Xue, Weiwei; Zhao, Zequn; Shi, Zhaokang; Wang, Weijie; Bai, Yu; Wang, Haoxue; Qiu, Peng; Xue, Jianfu; Chen, Baoguo (Frontiers in Plant Science, 2024)
Introduction：Nitrogen (N) plays a pivotal role in the growth, development, and yield of maize. An optimal N application rate is crucial for enhancing N and carbohydrate (C) accumulation in waxy maize grains, which in turn synergistically improves grain weight. Methods: A 2-year field experiment was conducted to evaluate the impact of different N application rates on two waxy maize varieties, Jinnuo20 (JN20) and Jindannuo41 (JDN41), during various grain filling stages. The applied N rates were 0 (N0), 120 (N1), 240 (N2), and 360 (N3) kg N ha-1. Results: The study revealed that N application significantly influenced nitrogen accumulation, protein components (gliadin, albumin, globulin, and glutelin), carbohydrate contents (soluble sugars, amylose, and amylopectin), and activities of enzymes related to N and C metabolism in waxy maize grains. Notable varietal differences in these parameters were observed. In both varieties, the N2 treatment consistently resulted in the highest values for almost all measured traits compared to the other N treatments. Specifically, the N2 treatment yielded an average increase in grain dry matter of 21.78% for JN20 and 17.11% for JDN41 compared to N0. The application of N positively influenced the activities of enzymes involved in C and N metabolism, enhancing the biosynthesis of grain protein, amylose, and amylopectin while decreasing the accumulation of soluble sugars. This modulation of the C/N ratio in the grains directly contributed to an increase in grain dry weight. Conclusion：Collectively, our findings underscore the critical role of N in regulating kernel N and C metabolism, thereby influencing dry matter accumulation in waxy maize grains during the grain filling stage.